Orthogonal Middle-up Approaches for Characterization of the Glycan Heterogeneity of Etanercept by Hydrophilic Interaction Chromatography Coupled to High-Resolution Mass Spectrometry - D'Atri, Valentina; Nováková, Lucie; Fekete, Szabolcs; Stoll, Dwight; Lauber, Matthew; Beck, Alain; Guillarme, Davy (Analytical chemistry, 2019)
Etanercept is a recombinant Fc fusion protein widely used to treat rheumatic diseases. This protein is highly glycosylated and contains numerous O- and N-glycosylation sites. Since glycosylation is recognized as an important critical quality attribute (CQA) that can affect immunogenicity, solubility, and stability of Fc fusion proteins, it should be thoroughly characterized. In this work, hydrophilic interaction chromatography (HILIC) was combined with high-resolution mass spectrometry (HRMS) by using a quadrupole time-of flight mass spectrometer to assess glycosylation of etanercept at the middle-up level of analysis (fragments of ca. 25-30 kDa). In addition, a combination of different enzymatic digestion procedures (i.e., glycosidase, sialidase, and protease) was systematically employed to facilitate spectra deconvolution. With the developed procedure, the main post-translational modifications (PTMs) of etanercept were assessed, and a global overview of the subunit-specific distribution of the glycosylation pattern was obtained at a middle-up level of analysis.
Keywords: Streptococcus pyogenes; Etanercept; Hydrophobic and Hydrophilic Interactions; Peptide Hydrolases; etanercept; Neuraminidase; bakteriální proteiny; neuraminidasa; glykosylace; Chromatography; Bacterial Proteins; chromatografie; Peptide-N4-(N-acetyl-beta-glucosaminyl) Asparagine Amidase; Glycosylation; hmotnostní spektrometrie; proteasy; glykopeptidasa; hydrofobní a hydrofilní interakce; Mass Spectrometry